2023
DOI: 10.3847/1538-4357/acb3c2
|View full text |Cite
|
Sign up to set email alerts
|

Target Selection and Validation of DESI Quasars

Abstract: The Dark Energy Spectroscopic Instrument (DESI) survey will measure large-scale structures using quasars as direct tracers of dark matter in the redshift range 0.9 < z < 2.1 and using Lyα forests in quasar spectra at z > 2.1. We present several methods to select candidate quasars for DESI, using input photometric imaging in three optical bands (g, r, z) from the DESI Legacy Imaging Surveys and two infrared bands (W1, W2) from the Wide-field Infrared Survey Explorer. These methods were extensively test… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 55 publications
0
52
0
Order By: Relevance
“…However, the seemingly unusual distribution of these sources in the system was difficult to interpret. Furthermore, the Dark Energy Spectroscopic Instrument targeting overlay in the Sky Viewer incorrectly suggested that the bulk of sources in this system were either quasars or emission line galaxies (see Chaussidon et al 2023 andRaichoor et al 2023 for details on the target selection and expected contamination rates for each class of objects).…”
Section: Delve J1448+1728 (Delve 5)mentioning
confidence: 99%
“…However, the seemingly unusual distribution of these sources in the system was difficult to interpret. Furthermore, the Dark Energy Spectroscopic Instrument targeting overlay in the Sky Viewer incorrectly suggested that the bulk of sources in this system were either quasars or emission line galaxies (see Chaussidon et al 2023 andRaichoor et al 2023 for details on the target selection and expected contamination rates for each class of objects).…”
Section: Delve J1448+1728 (Delve 5)mentioning
confidence: 99%
“…Interpreting the angular clustering or CMB lensing signal for a sample of quasars requires knowledge of the sample's redshift distribution. Targeted quasar redshift surveys are currently limited to optically bright relatively unobscured quasars (e.g., Lyke et al 2020;Alexander et al 2023;Chaussidon et al 2023), and individual blind redshift surveys lack either the breadth or depth to constrain the redshift distribution of our full sample. In order to obtain a nearly complete and statistically representative estimate of the redshifts of our sample quasars, we therefore look to the well-characterized Boötes and COSMOS (Scoville et al 2007) fields.…”
Section: Redshift Informationmentioning
confidence: 99%
“…Complementary papers describe the target selection for the dark-time DESI tracers (LRGs; Zhou et al 2023;ELGs;A. Raichoor et al 2023, in preparation;and QSOs;Chaussidon et al 2023) and the Milky Way Survey (MWS; Cooper et al 2023). Myers et al (2023) present how the target selections are implemented in DESI.…”
Section: Introductionmentioning
confidence: 99%